Taxonomic surrogacy in andean montane forests - Herrando Pérez, Salvador (2012)
Ecological surrogates are environmental or biotic proxies for biodiversity quantification. Their application circumvents logistic constraints and taxonomic voids to sample and identify species, and has become an important tool in conservation and management. In this study, we illustrate a surrogate method using multivariate ordinations, and we apply it to tree data from the Chanchamayo montane forest (Andes, Peru).